Solvent-free mechanosynthesis of Schiff bases derived from thiadiazole with potential application in sensing ionic species and NLO applications - C.U. Vite-Morales; M.Á. Amado-Briseño; R.A. Vázquez-García; J.E. Muñoz-Pérez; M.A. Veloz-Rodríguez; E. Rueda-Soriano; A. Espinosa-Roa; O.J. Hernández-Ortiz (Chemical Physics Impact)
In this work, we report the solvent-free mechanosynthesis of three Schiff bases (SBs) derived from 1,3,4-thiadiazole covalently bonded to indole (Th-In), quinoline (Th-Qn) and triphenylamine (Th-TPA) groups. This green chemistry method showed a drastic reduction in reaction time and avoidance of solvents for obtaining SBs, with good reaction yields. The molecular structures of SBs were investigated by computational chemistry calculations, with global reactivity parameters indicative of electron acceptor behavior, estimation of frontier molecular orbitals, and their theoretical band gaps of 3.49 and 3.4 eV for Th-In and Th-Qn, respectively, and the lowest of 299 eV for Th-TPA. To evaluate the possible NLO response, the hyperpolarizabilities (β) were also estimated, which are several orders of magnitude higher than the urea value used as a reference. The absorption and emission spectra were calculated using TD-DFT. These results showed a larger redshift for Th-TPA, with possible charge transfer processes more intense than those obtained for Th-In and Th-Qn. The photophysical properties of the Schiff bases were determined, with band gap values for Th-In, Th-Qn, and Th-TPA of 2.53, 2.66, and 2.39 eV in solution and 2.77, 2.26, and 2.21 eV in film, respectively. When the SBs were evaluated as potential naked-eye colorimetric chemosensors, colorimetric changes were observed in Fe2+, Fe3+, Pb2+, Cu2+, and Ag+ ions, with Ag+ being the most promising. Z-scan was used to evaluate the nonlinear response of the SBs and showed saturable absorber behavior with self-focusing processes. Cyclic voltammetry was used to determine the electrochemical band gaps, which were 2.70, 2.71, and 1.98 eV for Th-In, Th-Qn, and Th-TPA, respectively. Th-TPA exhibits superior optical and electrical properties among the three SBs investigated. In addition, it exhibits photochromism, which can be used in conjunction with its other properties in NLO and sensor applications.